2015
DOI: 10.1126/scitranslmed.3010286
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of the antihistamine chlorcyclizine and related compounds for treatment of hepatitis C virus infection

Abstract: Hepatitis C virus (HCV) infection affects an estimated 185 million people worldwide, with chronic infection often leading to liver cirrhosis and hepatocellular carcinoma. Although HCV is curable, there is an unmet need for the development of effective and affordable treatment options. Through a cell-based high-throughput screen, we identified chlorcyclizine HCl (CCZ), an over-the-counter drug for allergy symptoms, as a potent inhibitor of HCV infection. CCZ inhibited HCV infection in human hepatoma cells and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
137
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 50 publications
3
137
1
3
Order By: Relevance
“…called the NCGC Pharmaceutical Collection (NPC) (6), and a small group of clinically approved ion channel inhibitors used to treat cardiac or neurologic conditions (7). These independent studies identified several structurally related compounds as potent HCV cell entry inhibitors both in vitro and in vivo.…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
See 4 more Smart Citations
“…called the NCGC Pharmaceutical Collection (NPC) (6), and a small group of clinically approved ion channel inhibitors used to treat cardiac or neurologic conditions (7). These independent studies identified several structurally related compounds as potent HCV cell entry inhibitors both in vitro and in vivo.…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
“…Moreover, primary human hepatocytes do not express H 1 histamine receptor mRNA (40), although the antiviral activity of chlorcyclizine in these cells was readily detectable (6). Finally, histamine itself does not affect HCV infection, and two related compounds with divergent antihistamine activities have similar anti-HCV activities (6). Along the same lines, dopamine receptors and T-type Ca 2ϩ ion channels (CACNA1G, CACNA1H, CACNA1I) are not (or are poorly) expressed in Huh-7.5 cells (Ͻ0.18 reads per kilobase per million [RPKM]) (data not shown; T. Pietschmann, unpublished observation), in primary hepatocyte transcriptional profiles, and in human livers (the Human Protein Atlas [http://www.proteinatlas.org]).…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%
See 3 more Smart Citations